Comportamiento dinámico bajo impacto en micro-retículas poliméricas (2017)
The behavior of rubber-like polymer micro-reticles under impact loads from analytical, computational and experimental approaches to their behavior is studied. Based on work done in micro-reticles of other materials in quasi-static and dynamic conditions, an analytical model capable of predicting the impact absorption capacity of the cellular material is realized. The simulations are carried out in the software MARC MSCÃ with the appropriate boundary conditions, taking into account that there is only part of the structure because of the limitations of the software. All the experimental results are presented, from the characterization of the mechanical properties of the base material of the micro-reticles, to the compression tests and the impact of the cellular material. The experimental results are compared with the results obtained from the simulation and the analytical analysis, observing that these can predict the behavior of the cellular material successfully.